Empowerment y su efecto en la calidad del servicio del área de créditos hipotecarios del banco de la nación, agencia1 Trujillo, 2013 - Ly Layza, Jimmy Alexander (2015)
The purpose of the research is to determine the effect of empowerment on service quality in the area of mortgage loans from National Bank agency 1 Trujillo City. The aim of this study is to determine the effect of Empowerment in the services area of mortgage loans National Bank agent 1, Trujillo - 2013 ?. The hypothesis was formulated as follows: The Empowerment has significant effect on the quality of service in the area of mortgage loans from National Bank agent 1, Trujillo - 2013. In the study material has been sampled at the Agency Bank 1 nation of Trujillo, the techniques used for data collection were the survey and document analysis. Regarding the proposal of empowerment different strategies that make the stages that this program includes, each of the stages are interrelated in order to satisfy the customer who uses the services of the area of credits Banco de la Nacion observed . It concludes that empowerment is a management tool that significantly affects the quality of service in the area of mortgage loans from the National Bank. It is recommended that the area of mortgage loans from the National Bank will continue to implement the Empowerment for the benefits granted.